Public Debt Increase Challenge Under COVID-19 Pandemic Economic Crisis in the Caucasian Countries - VAKHTANG, CHARAIA; VLADIMER, PAPAVA (The journal of contemporary issues in business and government, 2021)
Paper provides an analysis of public debt problem in the Caucasusian countries of Armenia, Azerbaijan, Georgia, Iran, Russia and Turkey during the economic crisis under the COVID-19 pandemic. It also discussed some closely related issues, sauch as inflation, economic growth, employment, international rankings and etc. The paper analysis the different realities and perspectives of current and future developments of COVID-19 pandemic on selected countries economy. While recognizing that public debt increase was unavoidable during the global pandemic challenge, paper concludes that its effectiveness is hugely depended on when global economy can finally overcome the fact of being a hostage of COVID-19.